Full–scale experimental test for load–bearing behavior of the carbon fiber shell reinforced stagger–jointed shield tunnel. (1st May 2023) - Zhang, Xiaohui; Lin, Zhangrun; Zhang, Keping; Di, Honggui; He, Chao; Zhou, Shunhua
Abstract: Shield tunnels in the soft soil area are vulnerable to nearby engineering activities, resulting in deformation and damage problems. To investigate the effect of carbon fiber shells (CFS) on improving the loading bearing behavior of the tunnel under overloads, a full–scale experimental test is conducted and presented in this paper. Three rings of the stagger–jointed shield tunnel are chosen to be tested with twenty–four loads per ring applied to simulate the soil load and overload. Two loading processes are performed before and after the CFS are installed. Response data of the original tunnel and the CFS during the two loading processes are measured and analyzed. Main conclusions can be drawn as follows: (1) CFS reinforced tunnel has the same or even higher load–bearing capacity than the normal non–damaged tunnel. (2) The bonding effect between the CFS and the original tunnel is a critical parameter for the reinforced structure. The bending moment and axial force of the CFS reinforced tunnel are 33% and 20% smaller than those of the original tunnel before the CFS are detached. (3) The CFS can improve the bending resistance of the longitudinal joints which open at the intrados arc surface of the tunnel; however, no obvious effect is observed for those open at the extrados arc surface of the tunnel. (4) In the ultimate condition, the CFS is detached from the tunnel near the longitudinal joints which open at the intrados arc surface, and fractured partially near the longitudinal joints that open at the extrados arc surface of the tunnel. Highlights: A new CFS reinforcement method for the deformed and damaged tunnels is proposed. A full–scale experimental test on the stagger–jointed shield tunnel reinforced by CFS is conducted. Comprehensive responses data of the tunnel and the CFS are obtained. Failure characteristics of the reinforced structure is illustrated.